Motivated by LEAPS and bounds : analysing the effectiveness of the Ministry of Education's LEAPS model in cultivating prosocial attitudes in Singapore - Pei, Venus Ke Xin (Nanyang Technological University, 2022)
Much research has been conducted in the effectiveness of education as a key precedent of developing prosocial attitudes amongst students, but little attention has been paid to the specific components of education which are most influential in developing such attitudes. This study aims to investigate the key factors which lead to the development of prosocial attitudes in School. In particular, the subjective and objective performance under the LEAPS rewards system will be studied alongside other key variables. Public Service Motivation (PSM) will be measured to ascertain students’ prosocial attitudes. Using quantitative and qualitative methods, this paper found that rather than how well people performed under LEAPS, the intrinsic motivations related to volunteering in particular are more strongly associated with PSM, indicating the off-centred focus of the system. The paper recommends ways to redesign the system to cultivate prosocial attitudes so as to attain the goals of Singapore’s holistic education system.